Celiac Disease Symptom Resolution: Effectiveness of the Gluten-free Diet. Issue 1 (January 2018) - Sansotta, Naire; Amirikian, Karine; Guandalini, Stefano; Jericho, Hilary
ABSTRACT: Objective: The aim of the study was to evaluate the efficacy of the gluten-free diet (GFD) on gastrointestinal (GI) and extra-intestinal (EI) symptom resolution and identify predictors for persistence of symptoms in all celiac patients at the University of Chicago. Methods: We conducted a retrospective chart review from 2002 to 2015. GI symptoms included abdominal pain, bloating, constipation, diarrhea, failure to thrive/weight loss, nausea, reflux, and vomiting. EI symptoms included abnormal liver enzymes, arthralgia/arthritis, dermatitis herpetiformis, alopecia, fatigue, headache, anemia, stomatitis, myalgia, psychiatric disorders, rashes, seizures, neuropathy, short stature, delayed puberty, osteoporosis, and infertility. Results: A total of 554 patients (227 children) with celiac disease (CeD) were included. Abdominal pain, diarrhea and failure to thrive were the most common GI symptoms in children whereas diarrhea, bloating, and abdominal pain were most common in adults. Short stature, fatigue, and headache were the most common EI symptoms in children whereas iron deficiency anemia, fatigue, and headache/psychiatric disorders were most common in adults. Children had significantly higher rates of EI and GI symptom resolution as compared to adults, with greater rates of improvements in GI versus EI symptoms at more than 24 months. Long duration of symptoms, female sex, and non-adherence to a GFD were the most important significant predictors of failure to clinically improve. Conclusions: On a strict GFD, children report greater rates of both GI and EI symptom resolution as compared to adults with greater rates of improvement in GI over EI symptoms. Early recognition of CeD and close attention to diet adherence may help in symptom resolution. Abstract : Supplemental Digital Content is available in the text